The Relationship between Knowledge Intensity and Market Concentration in European Industries: An inverted U-Shape - Niels Krap; Johannes Stephan (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2008)
This paper is motivated by the European Union strategy to secure competitiveness for Europe in the globalising world by focussing on technological supremacy (the Lisbon - agenda). Parallel to that, the EU Commission is trying to take a more economic approach to competition policy in general and anti-trust policy in particular. Our analysis tries to establish the relationship between increasing knowledge intensity and the resulting market concentration: if the European Union economy is gradually shifting to a pattern of sectoral specialisation that features a bias on knowledge intensive sectors, then this may well have some influence on market concentration and competition policy would have to adjust not to counterfeit the Lisbon-agenda. Following a review of the available theoretical and empirical literature on the relationship between knowledge intensity and market structure, we use a larger Eurostat database to test the shape of this relationship. Assuming a causality that runs from knowledge to concentration, we show that the relationship between knowledge intensity and market structures is in fact different for knowledge intensive industries and we establish a non-linear, inverted U-curve shape.
urn:nbn:de:gbv:3:2-7288
Keywords: L16; L40; O33; 330; market structure; knowledge intensity; competition policy; Wissen; Industrie; Marktstruktur; Wirtschaftskonzentration; Lissabon Strategie; Wettbewerbspolitik; EU-Staaten